Some considerations on Phaedrus’ «veils’ play» and a possible reference to the Veiled Hippolytus - Lavilla de Lera, Jonathan (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2017)
The current paper has arisen as an appendix of a previous research on the Phaedrus of Plato. On that occasion, while we were working on a new commentary of the full dialogue, we had to consider the possible meanings of the passage in which Socrates veils his head to pronounce his fi rst speech on love (cf. Phdr. 237a4-5). As a result of that inquiry, a hypothesis came to our mind: could this text contain an implicit reference to the lost Veiled Hippolytus of Euripides? We did not go in depth on this matter, as it was not essential to grasp the meaning of the aforementioned passage. However, we did not forget about this possibility and the present paper tries to answer it. Even if it is not possible to proof that the Phaedrus alludes to the Veiled Hippolytus, there are some evidences that make this intertextuality possible. The main scope of this paper is to show them.